Shrouds of the night : masks of the Milky Way and our awesome new view of galaxies - Block, David L. (Springer, 2017)
Chapter 1. The Grand Stage Before Us: “The Sidereal Messenger”. Chapter 2. Cosmic Masks: Shrouds of the Night. Chapter 3. Detectives in Chile. Chapter 4. Chemical Factories Smaller than a Snowflake...